Plasmodium vivax malaria presenting with severe thrombocytopenia. - Makkar,RPS; Mukhopadhyay,S; Monga,A; Monga,A; Gupta,AK (Braz J Infect Dis, 2002)
Plasmodium falciparum and Plasmodium vivax malaria are endemic infections in India and are commonly associated with mild hematological abnormalities. Severe thrombocytopenia is common in isolated falciparum and mixed falciparum/vivax malaria, but is very rare in isolated P.vivax infection. We hereby report a case of severe thrombocytopenia (platelet count of 8x10(9)/L) in a case of vivax malaria. This is only the second case ever reported in the literature of such profound thrombocytopenia in a case of isolated P.vivax malaria.